2012
DOI: 10.1002/hipo.22037
|View full text |Cite
|
Sign up to set email alerts
|

Patterning of retinoic acid signaling and cell proliferation in the hippocampus

Abstract: The nuclear receptor ligand retinoic acid (RA) has been identified as an endogenous regulatory factor in the hippocampus, acting on pyramidal neurons and granule neuron progenitors, but almost nothing is known about the distribution of RA itself in the hippocampus. This study describes the source of RA for the rodent hippocampus in the meninges via the key RA synthetic enzyme retinaldehyde dehydrogenase 2 (RALDH2). Diffusion of RA from the meninges potentially creates a gradient of RA across the infrapyramidal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
48
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(55 citation statements)
references
References 85 publications
7
48
0
Order By: Relevance
“…RA has only recently been recognized to be active in the hypothalamus as a regulatory factor and the hypothalamus is one of the few brain regions in which RA functions, alongside regions such as the hippocampus and olfactory system (Goodman et al, 2012; Hagglund et al, 2006; Shearer et al, 2012a). However the importance of RA and its precursor, vitamin A, to control feeding and weight, was recognized much earlier.…”
Section: Discussionmentioning
confidence: 99%
“…RA has only recently been recognized to be active in the hypothalamus as a regulatory factor and the hypothalamus is one of the few brain regions in which RA functions, alongside regions such as the hippocampus and olfactory system (Goodman et al, 2012; Hagglund et al, 2006; Shearer et al, 2012a). However the importance of RA and its precursor, vitamin A, to control feeding and weight, was recognized much earlier.…”
Section: Discussionmentioning
confidence: 99%
“…Each reaction was run in triplicate on differentiating NE-4C (DIV2, 4,6,10,14), embryonic RGl or adult RGl (DIV4, DIV8) samples, as well as on nondifferentiated NE-4C or RGl (DIV0) samples. Amplification was performed in StepOnePlus (Applied Biosystems) equipment.…”
Section: Reverse Transcription For Real-time Pcrmentioning
confidence: 99%
“…RA has been reported to regulate neuron formation both in the embryonic, as well as in the postnatal/adult brain [1][2][3][4] and has been widely used as a potent inducer of neuronal differentiation in various multipotent cell populations (embryonic carcinoma cells, embryonic and neural stem cells, induced pluripotent stem cells), in vitro.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our present study was carried out on SH-SY5Y cells that have been differentiated with retinoic acid to exhibit neuronal features including cessation of cell division, development of long bipolar neuronal-like cellular processes and display of biochemical markers of neuronal differentiation (Pahlman et al 1984;Lopez-Carballo et al 2002; El Andaloussi-Lilja et al 2009). Retinoic acid, which we employ to trigger neuronal differentiation in SH-SY5Y cells, is an endogenous signaling molecule of neuronal differentiation during in vivo development of the nervous system (Jacobs et al 2006;Maden 2007;Goodman et al 2012). Live imaging demonstrated that following thermal stress, both YFP-HSPA6 and YFP-HSPA1A rapidly localized to centrioles in the cytoplasm of differentiated neurons.…”
Section: Discussionmentioning
confidence: 99%